THE CRITICAL PEDAGOGY AND THE ACADEMIC SUCCESS FOR EVERYONE - Adriana Aubert; Carme García (Ediciones Universidad de Salamanca, 2009)
Sometimes, some sectors of the critical pedagogy opposed social transformation- driven schools against measurable assessment. However, the number of educational projects that overcome this dualism is growing in Europe; the collaboration between both discourses do not imply a decrease of the strength any of them in order to give room to the other, but instead both gain in intensity. On the one hand, these are critical pedagogy projects rigorously based upon the social and educational transformative theories. On the other hand, these projects succeed in improving the results of all the children, both the results measurable with all kinds of evaluations and the nonmeasurable results, but yet assessable through the debate and dialogue among everyone involved: the social transformation of the environment created by the critical pedagogy orientation of these projects improves the measurable and non-measurable results.